2003
DOI: 10.1108/13522750310457348
|View full text |Cite
|
Sign up to set email alerts
|

Innovative use of the Internet in established small firms: the impact of knowledge management and organisational learning in accessing new opportunities

Abstract: In this article, three established small‐ and medium‐sized enterprises provide qualitative case study evidence of the extent to which information communications technology can be embedded within a firm’s marketing strategy, from the earliest adoption stages to the integration of the Internet with key business functions. These case studies also provide insights into the innovative ways that can be used to reposition a firm, its marketing strategy, services and products, both within the national and the global m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
1
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(127 citation statements)
references
References 18 publications
4
115
1
7
Order By: Relevance
“…Additionally, firms' Internet adoption research has focused to a large extent on large organizations. Internet adoption in many SMEs is manifested in websites which are viewed to provide the most value within an inherently marketing driven context (Marcolin et al, 2005;Martin and Matlay, 2003;Jones et al, 2003). While there is plenty of research that studied IT including the web and SMEs, there is limited research on adopting the web for marketing purposes.…”
Section: Internet Adoption By Smesmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, firms' Internet adoption research has focused to a large extent on large organizations. Internet adoption in many SMEs is manifested in websites which are viewed to provide the most value within an inherently marketing driven context (Marcolin et al, 2005;Martin and Matlay, 2003;Jones et al, 2003). While there is plenty of research that studied IT including the web and SMEs, there is limited research on adopting the web for marketing purposes.…”
Section: Internet Adoption By Smesmentioning
confidence: 99%
“…Moreover, the entrepreneurial orientation of SMEs owners/ managers was found to have a strong effect on their adoption of the web (Fillis and Wagner, 2005;Elliott and Boshoff, 2007). Similarly, Martin and Matlay (2003) found that website adoption stemmed from the SMEs owners/managers who recognized the importance and usefulness of websites in marketing. Bruque and Mayano (2007) based on their study on the determinants of information technology adoption and implementation in SMEs, found that top management support, growth experienced by the firm, attitude toward change and imitation of other firms were the main determinants.…”
Section: Internet Adoption By Smesmentioning
confidence: 99%
See 1 more Smart Citation
“…• The extent to which SME owner-managers participate in and get their eBusiness adoption and general business advice via informal, often highly social, business networks (Beckinsale et al, 2006;Gibbs et al, 2007;MacGregor & Vrazalic, 2007;Simmons et al, 2008) and/or get advice from family members (Galloway & Mochrie, 2005;Martin & Matlay, 2003;Simpson & Docherty, 2004;Zheng et al, 2004). This suggests SME owner-managers who are members of personal or business networks might be inclined to follow the advice of opinion leaders in or the norms of these networks concerning blog use.…”
Section: Which Sme Characteristics Are Suited To Blog Use?mentioning
confidence: 99%
“…• The extent to which SME owner-managers have good experiences with eBusiness solution providers, which is largely governed by the providers' eBusiness capability and knowledge (Martin & Matlay, 2003) and the providers' understanding of the SME owner-manager's business goals and needs (Brown & Lockett, 2004;Martin & Matlay, 2003;Simpson & Docherty, 2004). This suggests that it is the SME owner-managers who trust and value the advice of solution providers (if they are knowledgeable about the effective business use of blogs) who are more likely to use blogs in their business.…”
Section: Which Sme Characteristics Are Suited To Blog Use?mentioning
confidence: 99%